Comparative study on shear performance of blended pozzolonic RC beams with fly ash and recycled aggregates - Damera, Harikrishna; Murthy, N.R. Dakshina; Rao, N.V. Ramana (Journal of Structural Engineering, 2024)
Shear failure in a reinforced concrete beam is a sudden failure which is associated with crushing of concrete and is abrittle failure. A structural designer should be aware of various components of shear resisting mechanisms particularlythe shear resistance of concrete. In this regard, an experimental investigation was carried out on forty simply supportedreinforced concrete beams, to examine their shear performance of with and without shear reinforcement. This paperreports the results of a laboratory based experimental study aimed at studying shear performance of blended concretebeams with fly ash and recycled aggregates. Blended concrete beams of M35 and M45 grades were produced by partiallyreplacing the cement by 25 percent fly ash and the Natural Coarse Aggregates (NCA) were replaced by RecycledCoarse Aggregates (RCA) in different fractions of 0,25,50,75 and 100 percentages. The experimental shear strength ofblended concrete beams was then compared with predicted shear strength evaluated from various international codesand some existing empirical models in order to adjudicate the relevance of the experimental shear strength with thepredicted shear strengths for beams without shear reinforcement.